Socio-Epidemiological Perspectives of Sexual Trauma Experiences and Influential Factors on Sexual Orientation in Men Who Have Sex with Men - Sitorus, Rico Januar; Misnaniarti, Misnaniarti; Legiran, Legiran; Syakurah, Rizma Adlia; Sartika, Diana Dewi; Maharani, Asri; Patresia, Retta (UI Scholars Hub, 2025)
The complexity of sexuality and sexual trauma experiences, including harassment, unwanted touching, sexual urges, and forced sexual intercourse, should not be underestimated because of the tendency to initiate adverse psychosocial impacts. Sexual harassment can increase mental health risks, which may influence sexual orientation decisions. This quantitative study, using a cross-sectional design, aimed to determine a relationship between sexual trauma experiences and sexual orientation in men who have sex with men (MSM). This study population was MSM living in Palembang and Prabumulih City, with a sample size of 216 respondents. The proportion of respondents with homosexual orientation was 57.1%, and the proportion having sexual trauma experiences was 42.3%. The multiple logistic regression identified a significant relationship between sexual trauma experiences and sexual orientation in MSM with a pvalue of 0.02, an adjusted odds ratio of 2.71, and a 95% CI of 1.17-6.26. These results suggested a higher risk of a different sexual orientation among traumatized MSM compared to MSM without one after controlling access to pornographic content and correcting parenting patterns. Sexual trauma has been shown to affect individual sexual orientation; therefore, special attention is needed due to the impact on future life behavior.